2018
DOI: 10.1186/s40557-018-0268-2
|View full text |Cite
|
Sign up to set email alerts
|

An overview of compensated work-related injuries among Korean firefighters from 2010 to 2015

Abstract: BackgroundAlthough one in two firefighters in South Korea have experienced work-related injuries, there are few studies which show the overview description on work-related injuries and its analysis regarding such causes. Therefore, we aimed to show the overview of compensated work-related injuries in order to serve fundamental data for establishing prevention policies on work-related injuries for Korean firefighters.MethodsWe requested the all claimed work-related injury data of Korean firefighters from 2010 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…또한 우리나라 소방공무원의 우울증은 19.2∼39.7%에 달 하며 (National Fire Agency, 2008;Kim TW et al, 2010) 최근 5년간 소방공무원의 순직 및 공상자가 54.1% 증가한 것으로 조사되어(National Fire Agency, 2017) 각종 사고현 장의 최일선에서 일하는 소방공무원의 안전을 위협하는 요 소가 되고 있다.…”
unclassified
“…또한 우리나라 소방공무원의 우울증은 19.2∼39.7%에 달 하며 (National Fire Agency, 2008;Kim TW et al, 2010) 최근 5년간 소방공무원의 순직 및 공상자가 54.1% 증가한 것으로 조사되어(National Fire Agency, 2017) 각종 사고현 장의 최일선에서 일하는 소방공무원의 안전을 위협하는 요 소가 되고 있다.…”
unclassified
“…As well as, the workers with casual work contracts and domestic subcontractors may be less committed to the organization and perform their responsibility with lower attention and in turn, more cognitive failure. Based on the obtained results, the They showed that the scores of verbal memory, attention -concentration, immediate memory, and total learning were lower for the shift workers [28]. The results of a systematic review and meta-analysis show that the shift workers have a trend toward an increased risk of chronic sleep disturbances such as insomnia symptoms (risk ratio 1.16, 95% Confidence interval 0.97-1.38) [29].…”
Section: Discussionmentioning
confidence: 95%
“…Ozdemir et al investigated the effect of shift work on cognitive functions. They showed that the scores of verbal memory, attention – concentration, immediate memory, and total learning were lower for the shift workers [ 28 ]. The results of a systematic review and meta-analysis show that the shift workers have a trend toward an increased risk of chronic sleep disturbances such as insomnia symptoms (risk ratio 1.16, 95% Confidence interval 0.97–1.38) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These mainly involve sleeping, 14 , 15 depression and stress, 16 , 17 cognitive functions, 18 cancer, 19 , 20 hypertension, 21 physical activity and obesity, 22–24 metabolic syndromes, 25 and injuries and musculoskeletal disorders. 26 , 27 According to the 2154 work injuries that were recorded from 2010 to 2015 in South Korea in reference, 28 the majority of injuries concerned the upper and lower back (25.3%). Such study results were similar to the results of this study.…”
Section: Introductionmentioning
confidence: 99%